Estimation of vitamin D status and calcium level among pregnant women in Tikrit city: case control study - Tafaoul Jaber AL Jubory (Tikrit Journal of Pure Science, 2024)
The demand for calcium and vitamin D rises during pregnancy, increasing the chance of hypocalcemia and vitamin D deficiency. Hypocalcemia may be associated with pregnancy-related complications. This study thus sought to ascertain the frequency of hypocalcemia and vitamin D insufficiency in pregnant women seeking secondary care, as well as to explore the possible associations between these disorders and pregnancy outcomes.